The Effect Of Nurse’s Therapeutic Approach On Reducing The Anxiety Level Of Families Of Critically Ill Patients In The Icu - Yuana Dwi Agustin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Families of critically ill patients treated in the ICU often experience anxiety due to the patient's unstable condition, the intensive care environment, and communication limitations. The therapeutic approach of nurses is an empathetic communication strategy that can help reduce family anxiety. This study aims to determine the effect of the therapeutic approach of nurses on the anxiety levels of families of critically ill patients in the ICU. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 respondents, who were family members of critically ill patients selected using purposive sampling. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire and analyzed using the Wilcoxon Signed Rank Test. The results showed a significant decrease in anxiety levels after the therapeutic approach was implemented by nurses (p = 0.000 < 0.05). In conclusion, the therapeutic approach of nurses has a significant effect on reducing the anxiety levels of families of critically ill patients in the ICU. It is hoped that nurses will be able to consistently apply therapeutic communication in providing nursing care in the ICU.